Peripheral neuropathy as initial manifestation of Churg-Strauss Syndrome - Antonio Villa; Marianna Gregorio; Francesca Bassi; Ignazio Santilli (Journal of Health and Social Sciences)
Peripheral neuropathy is a well-known complication of primary systemic vasculitides that are characterized by inflammatory cell infiltration causing necrosis of blood vessels. Neurological complications in eosinophilic granulomatosis with polyangiitis (EGPA), previously known as Churg-Strauss syndrome, can be seen in 60-70% of cases, and in a portion of them neurological dysfunction may precede the involvement of other organs. An early recognition of this entity is the key to successful treatment and positive outcome. We report a case of Churg-Strauss syndrome in a young man with signs of rapidly evolving peripheral neuropathy. The diagnosis was established based on the hypereosinophilia, nasal polyposis, a positive biopsy and ANCA serology, without a history of asthma. In this case report, the peripheral neuropathy was the initial manifestation of the Churg-Strauss syndrome.